ASSESSING INTRAPRENEURIAL ASPECT IN ORGANIZATION (CASE STUDY PT XYZ IN INDONESIA) - Wirakanda, Gugum Gumilang; Pringgabayu, Dematria; Widyana, Suci Fika (Universitas Muhammadiyah Surakarta, 2019)
PT XYZ is a company which works in industry of oil and gas. With a lot of competition in the industry, PT XYZ needs to improve their performance especially in their main business line, Oil and Drilling Services Operation and also improve their Human Resources. One way to increase their performance is to know and improve the intrapreneurship in the company.This research is using qualitative approach. The first step conducted in this research was to look for the problem from the object being researched by the author. The data collections consist of primary data from questionnaire. There’ll be two questionnaire distributed. First one is Entrepreneurial Orientation Survey (EOS) to assess the current entrepreneurial condition in the company which distributed to the entire division of the company. The second one is Entrepreneurial Leadership Questionnaire (ELQ) which will asses the leader of the divisions with four types of intrapreneur leaders, Miners, Explorers, Accelerators and Integrators. ELQ was distributed in two key divisions, Division of Drilling and Oilfield Service as PT XYZ’s core business and Human Resources Division to manage PT XYZ’s employees. This research will analyze the EOS and ELQ’s results and compare the result of both divisions of ELQOn the basis of the results of this research, it can be concluded that PT XYZ has a good entrepreneurial. PT XYZ’s employees also able to accept entrepreneurial environtment within the company. PT XYZ is also perform above average in the market, able to compesate the employees, empower the employees and doing innovation in par with the competitors. PT XYZ’s employees are also have some understanding about entrepreneurial knowledge. The leader in the PT XYZ’s Human Resource Division is Accelerator type while the leader in Division of Drilling and Oilfield Service is Miner type.